2020
DOI: 10.1021/acsanm.9b02524
|View full text |Cite
|
Sign up to set email alerts
|

ReaxFF Simulations of Laser-Induced Graphene (LIG) Formation for Multifunctional Polymer Nanocomposites

Abstract: Irradiation of polymer films by a CO 2 infrared laser under ambient conditions converts the polymer into porous graphene or laser-induced graphene (LIG). Here, we simulate the formation of LIG from five different commercially available polymers using reactive molecular dynamics. We determined that the molecular structure of the parent polymer has a significant effect on the final graphitic structure. CO is liberated during the initial part of the LIG formation process when the polymer is converted into an amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 57 publications
3
88
0
Order By: Relevance
“…During the initial 0.2 ns of lasing, an amorphous structure is formed that grows into an ordered graphene structure with 6membered carbon rings ( Fig. 2a) [41]. This is in agreement with the results presented by Lin et al [40], where TEM demonstrated the ordered ring structure of graphene formed on the PI (Fig.…”
Section: A Transformation Processsupporting
confidence: 91%
See 4 more Smart Citations
“…During the initial 0.2 ns of lasing, an amorphous structure is formed that grows into an ordered graphene structure with 6membered carbon rings ( Fig. 2a) [41]. This is in agreement with the results presented by Lin et al [40], where TEM demonstrated the ordered ring structure of graphene formed on the PI (Fig.…”
Section: A Transformation Processsupporting
confidence: 91%
“…Both studies have also reported unusual structures containing 5-and 7-member rings, which is a result of steric stresses, the rapid formation and cooling of the graphene and trapping it in a higher energy state ( Fig. 2c, d) [40,41]. LIG formation has been generally confirmed via Raman and X-Ray Diffraction (XRD) analyses.…”
Section: A Transformation Processmentioning
confidence: 79%
See 3 more Smart Citations